Studi Komparasi Sistem Hubungan Industrial Dalam Ekonomi Konvensional Dan Dalam Ekonomi Islam - Sari, Kharina Putri; Mas’ud, Fuad (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2021)
Industrial relations in Indonesia continues to grow with many Islamic companies. This leads to a neccessary condition to take a review through a comparison between the conventional economic system and the Islamic economic system, so hopefully others parties have perspective not only on conventional aspect but also islamic economic perspective related to Industrial Relations. This is a qualitative study with method used in this research is library research with a comparative approach. This literature research explains and compares industrial relations systems in conventional economics and in Islamic economics. The data analysis technique used is descriptive-comparative. Data can be obtained by reviewing books, scientific works in print or electronic form, and all other written material. The author tries to describe the two research objects and analyze them and then compare the results of the two objects. The results showed a fundamental difference from the conventional way of life and the Islamic way of life. The differences between them can be categorised in terms of the rights and obligations of employers and workers, determination of wages, and the role of government. The differences in both viewpoints arise due to the foundational aspect.